2016
DOI: 10.4314/sajas.v45i5.3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the <i>in vitro</i> M fermentation of wasted cladodes (<i>Opuntia spp</i>.), lucerne and oat hays

Abstract: Wasted cladodes from the cactus pear (Opuntia ficus spp.) are an environmental nuisance, and alternative measures are required to utilize this product, such as utilizing it as a ruminant feedstuff. By simulating ruminal fermentation through in vitro gas production, the fermentation characteristics of dried cladodes were compared with that of lucerne hay and oat hay. A completely randomized design with six replications was used to assess the kinetic parameters of gas production (lag time, rate of gas production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
1
0
2
Order By: Relevance
“…The in vitro dry matter digestibility (IVDMD) content of O. species in this study showed highly significant (p < 0.001) differences among the cultivars and ranged from 68.25 to 87.3%, with an average of 78.61% (Table 2). IVDMD values in cactus pear cladodes ranging from 48.5 to 86.6% were similarly recorded by several authors) [19,22,39,[59][60][61][62]. The high digestibility of all nutrients in treated groups [63] can be taken from the point that cacti contain minerals, which may be associated with improvement in the digestibility of all nutrients [26,36,64].…”
Section: In Vitro-dry Matter Digestibility (Ivdmd)mentioning
confidence: 54%
“…The in vitro dry matter digestibility (IVDMD) content of O. species in this study showed highly significant (p < 0.001) differences among the cultivars and ranged from 68.25 to 87.3%, with an average of 78.61% (Table 2). IVDMD values in cactus pear cladodes ranging from 48.5 to 86.6% were similarly recorded by several authors) [19,22,39,[59][60][61][62]. The high digestibility of all nutrients in treated groups [63] can be taken from the point that cacti contain minerals, which may be associated with improvement in the digestibility of all nutrients [26,36,64].…”
Section: In Vitro-dry Matter Digestibility (Ivdmd)mentioning
confidence: 54%
“…La DIVMS de la mayoría de los desperdicios vegetales fue superior a 60 %. La biodegradabilidad de SO, LS y BOB inoculados con lodo anaerobio fue de 42, 49 y 55 % (Yan et al 2017) y la DIVMS de OF inoculado con líquido ruminal fue superior a 70 % (del Razo et al 2015). Sauer et al (2012) argumentan que el ecosistema ruminal puede ser una alternativa para la bioconversión de material lignocelulósico en combustibles y químicos, lo cual concuerda con la DIVMS inoculada con líquido ruminal.…”
Section: Fermentación In Vitrounclassified
“…De acuerdo con Eriksson et al (2015), la digestión anaerobia tiene gran potencial para reducir la emisión de GEI al capturar los gases generados y quemarlos; pero es necesario encontrar la opción más favorable entre las que se emplean para el manejo de desechos (vertederos, composteo, incineración y alimentación animal), de acuerdo con las propiedades de cada alimento. Por ejemplo, los desperdicios de OF son una opción en la alimentación de rumiantes (Pinos et al 2010, del Razo et al 2015, pero generan una cantidad considerable de CH4 de las 7 a las 12 h de incubación, si bien es menor (p ≤ 0.05) que la generada por BOV y BOB. Así, el manejo adecuado de excedentes vegetales y sus desperdicios puede disminuir la emisión de CH4 a la atmósfera y promover la explotación de fuentes energéticas renovables (di María et al 2015), no sólo a partir de los desperdicios vegetales que se depositan en los vertederos sino también donde éstos vegetales se cultivan.…”
Section: Concentración De Ch4unclassified